Increasing Teachers' Creativity Through Visionary Leadership, Religiosity, and Mutual Help - Siti Chaerijah Aurijah; Soewarto Hardhienata; Sri Setyaningsih (International Journal of Education, Information Technology, and Others, 2026)
This study employed a quantitative research approach using a survey method involving 219 elementary school teachers, selected through proportional random sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both the measurement model (outer model) and the structural model (inner model), as well as to examine the direct and indirect relationships among the research variables. The findings indicate that visionary leadership, religiosity, and mutual help each have a positive and significant effect on teachers' creativity. In addition, mutual help significantly mediates the relationships between visionary leadership and teachers' creativity as well as between religiosity and teachers' creativity, demonstrating the important role of collaborative culture in strengthening teachers' creative capacities. Collectively, these variables explain 64% of the variance in teachers' creativity, while the remaining 36% is influenced by other factors beyond the scope of this study. These findings suggest that enhancing teachers' creativity requires an integrated strategy that combines visionary school leadership, the strengthening of teachers' religiosity, and the cultivation of a collaborative school culture grounded in mutual help. Such synergy is expected to promote sustainable educational innovation and improve learning quality in response to the demands of twenty-first-century education.